Basic perspective drawing : a visual approach - Montague, John, 1944- (Hoboken, NJ : Wiley, 2005)
Provides a general orientation and overview of basic perspective drawing, and uses illustrations and text to address more specific problems and techniques.
Includes index.
Adult.
Adult
Keywords: Drawing -- Technique; Perspective; Drawing -- Technique; Perspective